Cognitive impairment in geriatric patients hospitalized in the conservative ward - Padykuła, Marlena; Kózka, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Cognitive functions are responsible for receiving, processing and using information from the outside world. Aim. The aim of the study is to evaluate cognitive impairment in geriatric patients hospitalised in conservative ward. Material and methods. The study includes a total of 118 patients treated in the conservative ward. The study used: Test of Cognitive Impairment, Scale of Everyday Activities, Scale of Complex Operations, Social Support Scale for the Elderly, Geriatric Depression Rating Scale, NHP questionnaire and self-designed questionnaire. The data were statistically analyzed using the statistical package PQStat ver. 1.6. Results. Cognitive impairment has been found in 69% of the respondents. A statistically significant association between cognitive impairment and age of the respondents (p = 0,0002) and their mode of admission to the hospital (p = 0,0378) has been remarked upon. However, no significant correlation between cognitive impairment and gender (p = 0,3421), level of education (p = 0,1783) and marital status (p = 0,606) has been found. The lower functional efficiency and depression were associated with a higher incidence of cognitive impairment. Analysis of the results has shown a relationship between the occurrence of cognitive impairment and social support (p = 0,0261) and health condition of life energy (p = 0,0501), mobility limitations (p = 0,0027), difficulties in professional work (p = 0,0010), housework (p = 0,0047), social life (p = 0,0002), sex life (p = 0,0001), interests and hobbies (p = 0,04415) and free time (p = 0,0095). Conclusions. Every geriatric patient should undergo a comprehensive geriatric assessment, due to the observed relationship between the occurrence of cognitive impairment and functional efficiency, depression, social support and quality of life in different areas of life.